2017
DOI: 10.1007/s00404-017-4467-9
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic hysterectomy for benign indications: clinical practice guideline

Abstract: PurposeSince the introduction of minimally invasive gynecologic surgery, the percentage of advanced laparoscopic procedures has greatly increased worldwide. It seems therefore, timely to standardize laparoscopic gynecologic care according to the principles of evidence-based medicine. With this goal in mind—the Dutch Society of Gynecological Endoscopic Surgery initiated in The Netherlands the development of a national guideline for laparoscopic hysterectomy (LH). This present article provides a summary of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 29 publications
4
13
0
Order By: Relevance
“…3 , 4 , 7 , 19 , 21 Vaginal hysterectomy is the most recommended and preferred route whenever feasible, with the least morbidity and better outcomes. 11 , 13 VH is mostly performed for pelvic organ prolapse and was true in our study as well where we performed VH exclusively for pelvic organ prolapse only (99.6%). 3 , 4 With the proper patient selection, Kovac et al performed VH in 98.9% (10,975 out of 11,094) patients with benign pathology, suggesting that abdominal and laparoscopic route might have been overused or misused.…”
Section: Discussionsupporting
confidence: 62%
“…3 , 4 , 7 , 19 , 21 Vaginal hysterectomy is the most recommended and preferred route whenever feasible, with the least morbidity and better outcomes. 11 , 13 VH is mostly performed for pelvic organ prolapse and was true in our study as well where we performed VH exclusively for pelvic organ prolapse only (99.6%). 3 , 4 With the proper patient selection, Kovac et al performed VH in 98.9% (10,975 out of 11,094) patients with benign pathology, suggesting that abdominal and laparoscopic route might have been overused or misused.…”
Section: Discussionsupporting
confidence: 62%
“…Depending on the choice of genital masculinizing procedure, this may involve the removal of the internal female reproductive organs. Vaginal hysterectomy (VH) with or without a bilateral salpingo-oophorectomy (BSO) is thought to have advantages over total laparoscopic hysterectomy (TLH) (Sandberg et al., 2017 ). Available data suggest that a VH or TLH and BSO for trans men is safe, not associated with any additional risks compared to TLH and BSO in cisgender women, and is correlated with improved quality of life (Kaiser et al., 2011 ; Louie & Moulder, 2017 ; Obedin-Maliver et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Clinical Practice Guidelines for Laparoscopic Hysterectomy for Benign Indications developed by the Dutch Society of Obstetrics and Gynecology (NVOG). The recommendations are unclear but they are all implied as strong [17]. The Guidelines for Laparoscopic Treatment of Ventral and Incisional Abdominal Wall Hernias (International Endohernia Society [IEHS])-Part 1 was developed using the Oxford hierarchy of evidence (Oxford Methodology) [18].…”
Section: Resultsmentioning
confidence: 99%
“…This suggested that the GRADE system of recommendation itself was not used as per the guidance document. On the contrary, the guidelines that used Oxford Methodology and the 'Bespoke' system (SAGES Guidelines for the Clinical Application of Laparoscopic Biliary Tract original article Surgery) had more recommendations with matching strength than different strength when re-evaluated using GRADE, which was 62.2% and 50.0% respectively, mainly due to the fact that that the guideline developers complied better with the criteria of the recommendation system, and that the system included a quality of evidence section similar to GRADE: the lowest level in both the systems would always be inadequate evidence and advises the physician to find alternatives [17,18,20]. There are two potential reasons for the differences in agreement between the study authors and us.…”
Section: Discussionmentioning
confidence: 99%